Renaming Indigenous Toponymy in Official Use in the Light of Contact Onomastic Theories - Helander, Kaisa Rautio (York University, 2009)
From the 1870’s, Norwegian authorities began to give instructions for the ways in which the indigenous Sámi toponymy had to be changed into Norwegian in official place name use. These instructions concerned especially place name use in land purchasing and mapping. According to the ‘Land Purchasing Act’, the land property had to have a Norwegian name even if in many cases the land properties had only a Sámi name in oral use. In mapping, the main rule for Norwegianizing the toponymy was to translate the Sámi names into the Norwegian language. In my paper, I will discuss the linguistic strategies which were used in creating the Norwegian place names in cases when these names were deliberately constructed for the purposes of renaming. As a starting point, the contact onomastic theories will be applied in discussion of methods of this type of conscious renaming policy.